The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/om0498044
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Addition of Arylboronic Acids and Arylsiloxanes to α,β-Unsaturated Carbonyl Compounds via Transmetalation to Dicationic Palladium(II) Complexes

Abstract: A high reactivity of dicationic palladium(II) complexes for transmetalation of organoboron and -silicon compounds was demonstrated in the 1,4-addition of arylboronic acids or arylsiloxanes to acyclic and cyclic enones. [Pd(dppe)(PhCN)2](SbF6)2 and nitrile-free catalysts prepared in situ from Pd(acac)2, dppben, and Cu(BF4)2·6H2O or oxidation of Pd(dba)2 with Cu(BF4)2·6H2O in the presence of dppe or dppben effectively catalyzed the reactions of arylboronic acids at room temperature and arylsiloxanes at 75 °C. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(100 citation statements)
references
References 64 publications
6
94
0
Order By: Relevance
“…The electronic effect on transmetalation of a series of para substituted arylboronic acids shows a negative value (À0:54), demonstrating that the donating substituents accelerate the reaction (Scheme 15). 75 Aromatic C-B or C-Si bond cleavage with water or halogens and cleavage of aromatic main metal-carbon bonds with cationic palladium or platinum complexes are believed to proceed through a chelated Wheland intermediate 102.…”
Section: Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic effect on transmetalation of a series of para substituted arylboronic acids shows a negative value (À0:54), demonstrating that the donating substituents accelerate the reaction (Scheme 15). 75 Aromatic C-B or C-Si bond cleavage with water or halogens and cleavage of aromatic main metal-carbon bonds with cationic palladium or platinum complexes are believed to proceed through a chelated Wheland intermediate 102.…”
Section: Gmentioning
confidence: 99%
“…For the corresponding palladium-catalyzed reactions of organoboron, -silicon, and -bismuth compounds, bisphosphines bridged by two carbons, such as chiraphos (116) and dipamp (117), result in high yields and high enantioselectivities. 75,[107][108][109][110][111][112][113][114][115][116] Performance of these chiral ligands for enantioselectivities is shown in Scheme 18. The binap ligand 115 achieves high enantioselectivities for both cyclic and acyclic substrates.…”
Section: Gmentioning
confidence: 99%
“…We found that arylboronic acids easily transmetalate to dicationic palladium(II) complexes such as [Pd(dppe)(PhCN)212+, in which 1,4-addition of arylboronic acids and arylsiloxanes to enones smoothly took place in an aqueous medium. [28][29][30][31][32][33][34] This review focuses on our efforts in rhodium(I) or palladium(II)-catalyzed addition reactions of aryl-and 1-alkenylboron, silicon and bismuth compounds to Two catalytic cycles for rhodium(I) and palladium(II) catalysts are shown in Figure 1 Thus, this effect of substituents can be best interpreted by assuming interaction of an empty d orbital of palladium with the 6 C-B bond rather than with the 7r-orbital of the aromatic ring (20). Vol.64 No.11 2006 ( 7 ) 3.…”
Section: Introductionmentioning
confidence: 99%
“…The different possibilities of transmetallation reaction that may take place in the second stage of the asymmetric SM reaction were assessed. It has been shown that the transmetallation step in a typical SM coupling reaction does not proceed without the nucleophilic additive, which enhances the electron density at the boron atom through its coordination and formation of boron-ate adduct [20,21,24,65,66]. In an aqueous solution of inorganic bases, the role of this nucleophile may be played by the hydroxyl anion.…”
Section: Transmetallationmentioning
confidence: 99%